Current Topics in Menopause - Dvornyk, Volodymyr (Bentham Science Publishers, 2013)
Menopause is a significant event in a woman's life as is generally considered as an indicator for senescence in women. Evidence suggests that menopause results in many psychological and postmenopausal health problems, such as anxiety, osteoporosis, cardiovascular disease, metabolic disorder and others. Menopausal symptoms and associated disorders are of great importance for public health as they influence the quality of life of affected individuals. Therefore proper management of menopause will definitely contribute to healthy aging and the overall well-being of women.This e-book reviews recent progress in the research and management of menopause and associated health problems. It provides comprehensive coverage of both clinical aspects and basic research of menopause. Topics covered in this e-book include research findings about risk factors for complex medical conditions associated with menopause along with the treatment options for these conditions, with particular emphasis on hormone replacement therapy (HRT). These conditions include osteoporosis, dementia, cardiovascular diseases, obesity and diabetes mellitus.Subsequent chapters detail on common oncological malignancies post menopause. The e-book concludes with a review of HRT treatment including its advantages and disadvantages followed by a review on risk factors, causes and complications of premature menopause occurring in women before an age of 40 years.This e-book is a valuable guide for medical researchers and gynecological professionals with a focus on the pathophysiology and treatment of this medical condition.